(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
The yearbooks and almanacs printed between the beginning of the Second World War andthe end of the Fifties collect rare and hardly accessible data on the Italian film industry andthe professionals involved in it. As such, they are both sources, whose use can be extremelyprofitable in production studies, and objects of investigation that might reveal the rhetoric and the discursive strategies through which different social actors have promoted an image of that production system as a fully-fledged and rationally organized industry. The article describes these yearbooks and interprets such discourses, in order to better understand the tensions that characterize this phase of important changes for the Italian film production.